Production of Polyvinyl Alcohol/Amoxicillin - Chitosan/Collagen Hybrid Bilayer Membranes for Regeneration of Gingival Tissues - Aydin, Ayca; Ulag, Songul; Nouri, Sabereh; Durasi, Elif; Arayici, Pelin Pelit; Tinaz, Gulgun Bosgelmez; Guncu, Mehmet Mucahit; Cakir, Rabia; Gunduz, Oguzhan; Ustundag, Cem Bulent (WILEY-V C H VERLAG GMBH, 2025)
Periodontal diseases, if untreated, can cause gum recession and tooth root exposure, resulting in infection and irreversible damage. Traditional treatments using autologous grafts are painful and often result in postoperative complications. Scaffolds offer a less invasive alternative, promoting cell proliferation and healing without additional surgery, thus enhancing comfort for patients and doctors. This study developed Chitosan (Chit)/Collagen (Col) film surfaces and drug-loaded Polyvinyl Alcohol (PVA)/Amoxicillin (AMX) nanofibers using solvent casting and electrospinning methods, respectively. The surfaces are characterized by scanning electron microscopy (SEM), mechanical testing, Fourier Transform Infrared Spectroscopy (FTIR), and differential scanning calorimetry (DSC). Biocompatibility and antimicrobial properties are assessed using NIH/3T3 fibroblast cells and bacterial cultures. SEM images confirmed the structural integrity of AMX-loaded 13% PVA nanofibers, while FTIR analysis validated the compositional integrity of PVA/AMX nanofibers and Chit/Col film hybrid surfaces. Cell studies showed over 90% viability for Chit/Col film + PVA/AMX nanofiber hybrid bilayer membranes, confirming their biocompatibility. The antimicrobial assessment indicated that the Chit/Col film + PVA/AMX (0.2%) nanofiber hybrid bilayer membrane exhibited superior efficacy against Streptococcus mutans. These findings suggest that this hybrid bilayer membrane can enhance cell growth, promote proliferation, and enable controlled drug release, offering significant promise for regeneration of gingival tissues.
Keywords: biocompatibility; chitosan/collagen films; periodontal diseases; PVA/Amoxicillin nanofibers; scaffolds; IN-VITRO; NANOFIBERS; DISEASE; ALCOHOL; FILMS; Biochemistry & Molecular Biology; Materials Science; Polymer Science